An Asian introduction to the New Testament - Thomaskutty, Johnson 1972-; Sugirtharajah, Rasiah S. ca. 20./21. Jh.; Gupta, Nijay K. 1978- (Minneapolis, Minnesota Fortress Press, 2022)
As the Asian context is the cradle of many of the world's religions, the New Testament writings should be interpreted and reinterpreted by accepting their pluriform religious and ideological aspects. Moreover, the existence of multiple Christian denominations demands a doctrinally and conceptually balanced interpretation of the Scriptures. This book will demonstrate inclusive biblical claims within multireligious and multidenominational contexts
The book of Revelation / Biju Chacko.
Includes bibliographical references and index
Keywords: Bible -- Introductions; Bible; Christianity and culture -- Asia; Christianity and culture; Introductions; Asia